Gender differentials and old age survival in the Nairobi slums, Kenya - Bennett, Rachel; Chepngeno-Langat, Gloria; Evandrou, Maria; Falkingham, Jane (Social Science & Medicine, 2016)
This paper examines gender differentials in survival amongst older people (50+ years) in the Nairobi slums and to the best of our knowledge is the first study of its kind in an urban African setting. The results provide evidence contrary to the expected paradox of poorer self-rated health yet better survival amongst older women. Older women in the Nairobi slums have poorer self-rated health and poorer circumstances across other factors, including disability and socio-economic status. Further, older women in the slums do not have better survival. The conventional female advantage in mortality only becomes apparent after accounting for the cumulative influence of individual characteristics, social networks, health and socio-economic status, suggesting the female advantage in unadjusted old-age mortality does not apply to contexts where women experience significant disadvantage across multiple life domains. This highlights the urgent need to redress the support, status and opportunities available for women across the life course in contexts such as the Nairobi slums. In addition, a greater number of factors differentiate mortality risk amongst men than amongst women, suggesting inequality amongst slum dwelling older men and highlighting the need for gender sensitive interventions which account for the particular needs of both genders in old age.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; bidonvilles; environnement; inégalités; kenya; personnes âgées; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; santé; sexisme; systèmes d'oppressions; thématiques

A gendered human rights analysis of Ebola and Zika: Locating gender in global health emergencies - Davies, Sara E.; Bennett, Belinda (International Affairs, 2016)
Globally gender remains a key factor in differing health outcomes for men and women. This article analyses the particular relevance of gender for debates about global health and the role for international human rights law in supporting improved health outcomes during public health emergencies. Looking specifically at the recent Ebola and Zika outbreaks, what we find particularly troubling in both cases is the paucity of engagement with human rights language and the diverse backgrounds of women in these locations of crisis, when women-specific advice was being issued. We find the lessons that should have been learnt from the Ebola experience have not been applied in the Zika outbreak and there remains a disconnect between the international public health advice being issued and the experience of pervasive structural gender inequalities among those experiencing the crises. In both cases we find that responses at the outbreak of the crisis presume that women have economic, social or regulatory options to exercise the autonomy contained in international advice. The problem in the case of both Ebola and Zika has been that leaving structural gender inequalities out of the crisis response has further compounded those inequalities. The article argues for a contextual human rights analysis that takes into account gender as a social and economic determinant of health.
https://academic.oup.com/ia/article/92/5/1041/2688120
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; amérique latine; amériques; approches et analyses; care; droits des femmes*; inégalités; périodes historiques; ressource en ligne; régions géographiques; santé; santé publique; systèmes d'oppressions; thématiques